TRENDS OF SEXUAL ASSAULT CASES (Journal of Forensic Medicine & Toxicology, 2024)
The World Health Organization defines sexual violence as “any sexual act, attempt to obtain a sexual act, or other act directed against a person’s sexuality using coercion, by any person regardless of their relationship to the victim, in any setting”. This includes rape, indecent assault, sexual harassment and threats. This study was conducted in the casualty unit over a period of two years (September 2018 to September 2020), total 35 cases of directed against a person’s sexuality using coercion, by any person regardless of their relationship to the victim, in any setting” This includes rape, indecent assault, sexual harassment and threats.
Keywords: victim; World Health Organization